Ovis dalli subsp. dalli Nelson 1884 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ovis dalli subsp. dalli Nelson 1884 Ovis dalli subsp. dalli Nelson 1884, Proc. U. S. Natl. Mus., 7: 13. Type Locality: USA, Alaska, "killed by the Indians on some mountains south of Fort Yukon, and on the west bank of the river"; interpreted as "Mountains west of Fort Reliance, Alaska, on divide between Tanana and Yukon Rivers" (Miller, 1924:497), or "Mountains south of Fort Yukon on west bank of Yukon River, Alaska; probably Tanana Hills" (Miller and Kellog, 1955:823). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 710, DOI: 10.5281/zenodo.7316519